Design and Development of a Security and Guidance Robot for Employment in a Mall - Trovato, G.; López, A.; Paredes, R.; Quiroz, D.; Cuellar, F. (World Scientific Publishing, 2019)
Among the possible fields in human society in which robotics can be applied, the possibility of a robotic guard has been imagined since long time. Human guards usually perform a range of tasks in which a robot can provide help. Security personnel not only perform security tasks and patrolling services, but also have to interact with people, providing additional information about the area they safeguard. In this paper, we present the design, development and preliminary tests of RobotMan, an anthropomorphic robot commissioned by a security company that should serve in security roles, such as patrolling large indoor areas and acting as a telepresence platform for the human guards, and guidance roles such as welcoming visitors and providing information. In the preliminary experiment, the new robot and a human guard were employed the roles of security and guidance in a manufacturing center. The results of the experiment collected from 96 participants highlighted differences in participants’ behavior when interacting with the robot rather than the human and a different perception of likeability and authority of the robot depending on subtle differences in its appearance and behavior. These results provide useful indication for the employment of robot guards in a real world situation.
Keywords: Patrolling; Guard (computer science); Robot; Computer science; Security guard; Computer security; Robotics; Human–computer interaction; Perception; Artificial intelligence; Human–robot interaction; Law; https://purl.org/pe-repo/ocde/ford#2.12.00